Pengaruh Brand Ambassador, Brand Image, dan Online Customer Review Terhadap Keputusan Pembelian pada Produk Scarlett Whitening (Studi Kasus Konsumen Scarlett Whitening di Solo Raya) - Stefi, Alma Dhea; MG Sukamdiani, SE.,MM; Ngaisah (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
This study aims to examine the influence of brand envoys, brand pictures, and online client surveys on the purchase choice of Scarlett Brightening goods in Mandiri Raya. The type of research used is quantitative by distributing polls through Google Structure to 100 respondents who have purchased Scarlett Brightening items. Sample determination using purposive. The data analysis technique uses multiple regression analysis and t-test tests. The results of the data analysis show that Brand Ambassador (X1) has a partial and significant effect on the Purchase Decision (Y) on Scarlett Whitening products. Brand Image (X2) has a partial and significant effect on the Purchase Decision (Y) of Scarlett Whitening products. Online Customer Review (X3) has a partial and significant effect on Purchase Decision (Y) on Scarlett Whitening products. Brand Ambassador (X1), Brand Image (X2), Online Customer Review (X3) have a simultaneous and significant effect on Purchase Decision (Y) on Scarlett Whitening products (case study on Scarlett Whitening consumers in Solo Raya)